2008
DOI: 10.1590/s1516-35982008000600005
|View full text |Cite
|
Sign up to set email alerts
|

Relação fósforo e magnésio na fertilidade do solo, no estado nutricional e na produção da alfafa

Abstract: RESUMO -Com o objetivo de avaliar a influência da relação P:Mg na fertilidade do solo, no estado nutricional e na produção de matéria seca da alfafa, foi realizado um experimento em vasos com Latossolo Vermelho Amarelo distrófico, segundo delineamento inteiramente casualizado, em esquema de parcelas subdivididas, com três repetições. Os tratamentos foram constituídos de combinações de P (doses: 0, 100, 200 e 400 mg kg -1 , fonte: superfosfato triplo) e Mg (doses: 0, 100 e 200 mg kg -1 , fonte: cloreto de magné… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
4
0
2
Order By: Relevance
“…These values could be used as a reference to define suitable levels of these elements in the soil and plants. Moreira et al (2008), analyzing the P:Mg ratio in alfalfa, observed a positive relationship between these elements and the DMY. …”
Section: Resultsmentioning
confidence: 96%
“…These values could be used as a reference to define suitable levels of these elements in the soil and plants. Moreira et al (2008), analyzing the P:Mg ratio in alfalfa, observed a positive relationship between these elements and the DMY. …”
Section: Resultsmentioning
confidence: 96%
“…By lowering the pH of the medium is lowered, the solubility of elements as free hydrated cations is likely to occur. This behavior can be explained by some factors: (i) competition between cations for sorption, (ii) a decrease in the negative charge of complexes normally formed in a basic medium, and (iii) dissolution of soil components and consequent release to the external medium, harming the fixation of the chemical elements. , The typical behavior observed when increasing soil pH is that the sorption of cations also increases, following the sorption mechanisms, inner sphere surface complexation, and/or precipitation and multinuclear type reactions. , Also, the availability of nutrients in the soil varies according to the pH of the water and maximized in the pH range of 6 to 7 for potassium, calcium, magnesium, nitrogen, boron, sulfur, and phosphorus. , This result is interesting to observe the similarities between the dynamics of chemical elements in water and soil.…”
Section: Resultsmentioning
confidence: 99%
“…Em relação à deficiência de P, Zhong et al (1993) demonstraram que a formação de fosfatos de magnésio aumentou a absorção de Mg em Ricinus sp. cultivada em solução nutritiva, demonstrando que o P possui efeito sinérgico na absorção de Ca, Mg (Moreira et al, 2008) e Mn (Büll et al, 2008).…”
Section: Cation Exchange Capacity Of Oat Root Cultivated With and Witunclassified